Development and validation of the Referee Training Activity Questionnaire (RTAQ): Towards a better understanding of the training practices of soccer officials - McEwan, G. P.; Unnithan, V.; Easton, C.; Arthur, R. (Journal of Sports Sciences, 2020)
To develop and assess the validity of the Referee Training Activity Questionnaire (RTAQ), a systematic process was employed: 1) item generation; 2) assessments of content and face validity; and 3) assessments of criterion validity. In stage 1, items were generated following semi-structured interviews with an expert panel (n = 8). Following content analyses, the RTAQ was developed and comprised 3 primary sections (12 sub-sections) assessing: 1) attributes perceived to underpin soccer officiating performance; 2) general training information; and 3) specific training practices. In stage 2, the preliminary RTAQ was assessed for content and face validity by a sample of experts (n = 6). Based upon the content validity index (CVI), content validity was confirmed for 8 sub-sections (CVI = 0.78) with 5 sub-sections being deemed invalid (CVI < 0.78). Various amendments were carried out in accordance with participant feedback. In stage 3, the RTAQ was completed by a cohort of officials (n = 25) who subsequently recorded a detailed training diary. Negligible mean biases, wide 95% LOA, and significant Pearson correlations were observed between the RTAQ and training diaries for most training activities, suggesting the RTAQ holds promise as a useful and effective alternative of acquiring insight into the training practices of soccer officials.